U.S. Savings Banks' Demutualization and Depositor Welfare - Mattia Girotti; Richard Meade (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
Originally, U.S. savings banks were owned by their depositors. In recent decades, many savings banks have "demutualized", by converting from customer to investor ownership. We examine the implications of such events for depositor welfare. We introduce a random coefficients logit model of bank account choice and estimate depositors' tastes for bank characteristics (including banks' ownership type). We then measure the effect on depositor welfare of a simulated demutualization of all customer-owned savings banks. We find that depositors' welfare would increase on average. In particular, if demutualize savings banks offered a deposit rate in line with existing demutualized banks, each depositor would gain 1.14 annually, for a total of 22 million for each state and year.
Keywords: D12; G21; L21; P13; 330; Banks; Deposits; Demand Estimation; Customer Ownership; Mutuals